2014
DOI: 10.5902/1980509815746
|View full text |Cite
|
Sign up to set email alerts
|

EFECTO DEL RALEO SOBRE EL CRECIMIENTO Y LA DENSIDAD DE LA MADERA DE <i>Pinus taeda</i> IMPLANTADO EN MISIONES, ARGENTINA

Abstract: RESUMENEl mayor incremento en crecimiento de la plantación puede causar variación en las propiedades físicas de la madera, pudiendo disminuir la calidad de la misma para la industria. El objetivo del presente trabajo es evaluar el efecto de los tratamientos de raleo sobre el crecimiento y densidad de la madera de Pinus taeda implantado en Misiones, Argentina (25º 59'S -54º24'O). La plantación se estableció en 1985 con densidad inicial de 1644 pl.ha -1 y se manejó con tres intensidades de raleo (0, 33 y 66 % de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Research work on pruning and stand-thinning in forest plantations carried out by Espinosa et al [20], Ferrere et al, [21] and Martiarena et al [22] reported that the controls were always inferior to the treatments handled, bearing in mind that the authors mentioned above treated to improve the performance and quality of the wood. …”
Section: Rfrmentioning
confidence: 99%
“…Research work on pruning and stand-thinning in forest plantations carried out by Espinosa et al [20], Ferrere et al, [21] and Martiarena et al [22] reported that the controls were always inferior to the treatments handled, bearing in mind that the authors mentioned above treated to improve the performance and quality of the wood. …”
Section: Rfrmentioning
confidence: 99%